Side Effects of Labor Market Policies - Marco Caliendo; Robert Mahlstedt; Gerard J. van den Berg; Johan Vikström (Institute of Labor Economics (IZA), 2020)
Labor market policy tools such as training and sanctions are commonly used to help bring workers back to work. By analogy to medical treatments, the individual exposure to these tools may have side effects. We study effects on health using individual-level population registers on labor market events outcomes, drug prescriptions and sickness absence, comparing outcomes before and after exposure to training and sanctions. We find that training improves cardiovascular and mental health and lowers sickness absence. The results suggest that this is not due to improved employment prospects but rather to instantaneous features of participation such as, perhaps, the adoption of a more rigorous daily routine. Unemployment benefits sanctions cause a short-run deterioration of mental health, possibly due higher stress levels, but this tapers out quickly.
Keywords: J68; I12; I18; H51; 330; unemployment; health; sickness; prescriptions; mental health; drugs; training; depression; cardiovascular disease; sanctions